Coupling of lattice-Boltzmann solvers with suspended particles using the MPI intercommunication framework. (September 2017) - Puurtinen, T.A.; Toivanen, J.I.; Mattila, K.; Hyväluoma, J.; Nash, R.W.; Coveney, P.V.; Timonen, J.
Highlights: Strong and weak scaling of two coupled LB/particle dynamics solvers is tested. MPI intercommunication is used as a framework for the coupling. No clear performance loss due to coupling seen in the tests up to 4000 cores. Abstract: The MPI intercommunication framework was used for coupling of two lattice-Boltzmann solvers with suspended particles, which model advection and diffusion respectively of these particles in a carrier fluid. Simulation domain was divided into two parts, one with advection and diffusion, and the other with diffusion only (no macroscopic flow). Particles were exchanged between these domains at their common boundary by a direct process to process communication. By analysing weak and strong scaling, it was shown that the linear scaling characteristics of the lattice-Boltzmann solvers were not compromised by their coupling.